EGFR/Ras signaling controls drosophila intestinal stem cell proliferation via capicua-regulated genes - Jin, Yinhua; Ha, Nati; Xiang, Jinyi; Maldera, Julieta; Edgar, Bruce (PLoS Genetics, 2015)
Epithelial renewal in the Drosophila intestine is orchestrated by Intestinal Stem Cells (ISCs). Following damage or stress the intestinal epithelium produces ligands that activate the epidermal growth factor receptor (EGFR) in ISCs. This promotes their growth and division and, thereby, epithelial regeneration. Here we demonstrate that the HMG-box transcriptional repressor, Capicua (Cic), mediates these functions of EGFR signaling. Depleting Cic in ISCs activated them for division, whereas overexpressed Cic inhibited ISC proliferation and midgut regeneration. Epistasis tests showed that Cic acted as an essential downstream effector of EGFR/Ras signaling, and immunofluorescence showed that Cic’s nuclear localization was regulated by EGFR signaling. ISC-specific mRNA expression profiling and DNA binding mapping using DamID indicated that Cic represses cell proliferation via direct targets including string (Cdc25), Cyclin E, and the ETS domain transcription factors Ets21C and Pointed (pnt). pnt was required for ISC over-proliferation following Cic depletion, and ectopic pnt restored ISC proliferation even in the presence of overexpressed dominant-active Cic. These studies identify Cic, Pnt, and Ets21C as critical downstream effectors of EGFR signaling in Drosophila ISCs.